Reduced Gray Matter Volume Is Associated With Poorer Instrumental Activities of Daily Living Performance in Heart Failure. Issue 1 (January 2016) - Alosco, Michael L.; Brickman, Adam M.; Spitznagel, Mary Beth; Narkhede, Atul; Griffith, Erica Y.; Cohen, Ronald; Sweet, Lawrence H.; Josephson, Richard; Hughes, Joel; Gunstad, John
Abstract : Background: Heart failure patients require assistance with instrumental activities of daily living in part because of the high rates of cognitive impairment in this population. Structural brain insult (eg, reduced gray matter volume) is theorized to underlie cognitive dysfunction in heart failure, although no study has examined the association among gray matter, cognition, and instrumental activities of daily living in heart failure. Objectives: The aim of this study was to investigate the associations among gray matter volume, cognitive function, and functional ability in heart failure. Methods: A total of 81 heart failure patients completed a cognitive test battery and the Lawton-Brody self-report questionnaire to assess instrumental activities of daily living. Participants underwent magnetic resonance imaging to quantify total gray matter and subcortical gray matter volume. Results: Impairments in instrumental activities of daily living were common in this sample of HF patients. Regression analyses controlling for demographic and medical confounders showed that smaller total gray matter volume predicted decreased scores on the instrumental activities of daily living composite, with specific associations noted for medication management and independence in driving. Interaction analyses showed that reduced total gray matter volume interacted with worse attention/executive function and memory to negatively impact instrumental activities of daily living. Conclusions: Smaller gray matter volume is associated with greater impairment in instrumental activities of daily living in persons with heart failure, possibly via cognitive dysfunction. Prospective studies are needed to clarify the utility of clinical correlates of gray matter volume (eg, cognitive dysfunction) in identifying heart failure patients at risk for functional decline and determine whether interventions that target improved brain and cognitive function can preserve functional independence in this high-risk population.